From Rash Decisions to Critical Conditions: A Systematic Review of Dermatological Presentations in Emergency Departments - Algarni, Abdullah S.; Alshiakh, Safinaz M.; Alghamdi, Sara M.; Alahmadi, Mohammed A.; Bokhari, Abdulah W.; Aljubayri, Samar N.; Almutairy, Waad M.; Alfahmi, Najwa M.; Samargandi, Ramy (Diagnostics (Basel), 2025)
Background: Dermatological emergencies are critical conditions requiring immediate attention due to their potential to escalate into life-threatening scenarios. Accurate diagnosis and timely management are essential to prevent severe complications, including systemic involvement and mortality. This systematic review summarizes findings on dermatological emergencies in emergency departments (EDs), focusing on diagnostic accuracy, hospitalization rates, systemic complications, and management strategies. Methods: A systematic literature review of studies on dermatological emergencies was conducted, encompassing 24 prospective and retrospective cohort studies, cross-sectional studies, and descriptive analyses. The review included diverse patient populations, examining dermatological presentations, diagnostic methods, treatment strategies, hospitalization rates, and adverse outcomes. Key outcome measures such as diagnostic accuracy, complications, mortality rates, and re-visit frequencies were analyzed. Results: The studies revealed high diagnostic accuracy, particularly in in-person evaluations, with teledermatology showing slightly lower but reliable rates. Systemic complications, including severe drug reactions, bacterial infections, and autoimmune diseases, were common causes of hospitalization. Mortality rates varied, with conditions such as toxic epidermal necrolysis showing the highest risk. Hospitalization rates averaged 4.52%, and re-visit rates ranged from 1% to 6.5%. The results also highlighted the impact of environmental factors and seasonal trends on dermatological presentations. Conclusions: Dermatological emergencies pose significant challenges in emergency care. High diagnostic accuracy and effective management strategies are crucial in preventing severe outcomes. Timely diagnosis, careful management of systemic complications, and teledermatology play critical roles in improving care. Future research should focus on standardized management protocols, telemedicine applications, and the influence of environmental and demographic factors to enhance patient outcomes.